Analgesic Effects of Pre-induction Low-dose Ketamine on Post-tonsillectomy Patients (Journal of Enam Medical College, 2018)
Background: Post-operative pain management aims to decrease pain intensity with patient comfort and to improve post-operative outcome. Multimodal analgesia is currently recommended for effective post-operative pain control with lower total doses of analgesics and fewer side effects.Objective: To compare the analgesic effect of pre-induction low-dose ketamine against conventional general anaesthesia.Materials and Methods: This prospective comparative study was conducted over a period of 12 months at Combined Military Hospital, Dhaka. Two hundred and forty patients of either sex requiring tonsillectomy were divided into two groups: conventional general anaesthesia (control group) and general anaesthesia with low-dose ketamine (ketamine group). Non-invasive blood pressure, heart rate and SpO2 were recorded at regular intervals throughout the anaesthetic period. Post-operative analgesia was provided for both the groups using pethidine intramuscularly. Time to complete operation, pain intensity, time to request for first analgesia were noted and total opioid consumption and complications, if any occurred in 24 hours post-operatively, were also recorded and addressed accordingly.Results: The demographic data and mean operation time were similar in both the groups (p>0.05).Time to request for first analgesia was longer in lowdose ketamine group (mean ± SD 5.36±3.21 hours) than in control group (mean ± SD 2.49±1.53 hours) (p